Chitin: a comparison between its main sources - Izadi, Hamzeh; Asadi, Homa; Bemani, Marjan (Frontiers in Materials, 2025)
Chitin is the second most abundant polysaccharide on Earth, after cellulose, and it is mainly obtained from the shells of crustaceans. While chitin is currently derived from shrimp shells, there is a growing interest in commercializing chitin sourced from insects. This review compares chitin from various sources, including crustaceans, insects, fungi, and mollusks, based on several factors: purity, molecular weight, crystallinity, cost, and sustainability. Although crustaceans yield higher amounts of chitin and exhibit better crystallinity, insects present significant advantages in terms of sustainability, ease of extraction, and lower impurity levels. Chitin derived from insects is emerging as a sustainable alternative due to its simpler extraction processes and reduced environmental impact. This work highlights the increasing potential of insects as a reliable source for sustainable chitin production.